2016
DOI: 10.1038/nature16955
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM reveals a novel octameric integrase structure for betaretroviral intasome function

Abstract: Retroviral integrase (IN) catalyzes the integration of viral DNA (vDNA) into host target (tDNA), which is an essential step in the lifecycle of all retroviruses1. Prior structural characterization of IN-vDNA complexes, or intasomes, from the spumavirus prototype foamy virus (PFV) revealed a functional IN tetramer2–5, and it is generally believed that intasomes derived from other retroviral genera will employ tetrameric IN6–9. However, the intasomes of orthoretroviruses, which include all known pathogenic speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
152
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(159 citation statements)
references
References 59 publications
(73 reference statements)
7
152
0
Order By: Relevance
“…vDNAs play a key role in intasome assembly, which is required for HIV-1 IN to exert its enzymatic function (33)(34)(35). In line with this finding, vRNA might play a critical role in vRNP complex assembly.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…vDNAs play a key role in intasome assembly, which is required for HIV-1 IN to exert its enzymatic function (33)(34)(35). In line with this finding, vRNA might play a critical role in vRNP complex assembly.…”
Section: Discussionsupporting
confidence: 63%
“…Structure analyses have revealed that each HIV-1 IN domain (28)(29)(30) and the two domains composing the NTD-CCD (31) or the CCD-CTD (32) assemble into either a dimer or a tetramer form. Recently, the entire structures of other retroviral INs in a complex with their cognate viral DNA ends, referred to as intasomes, have been successfully resolved (33)(34)(35). These structure analyses of intasomes revealed the unprecedented assembly of INs into a tetramer form for the prototype foamy virus (33) and octamer forms for the Rous sarcoma virus (34) and mouse mammary tumor virus (35), providing new insights into the enzymatic role for IN during retroviral DNA integration and the inhibitory results of INSTI (36).…”
mentioning
confidence: 99%
“…However, recent intasome structures from four orthoretroviruses revealed both striking complexity and diversity. Reported from February 2016 to January 2017, the new structures elucidated intasomes from the β-retrovirus mouse mammary tumor virus (MMTV) [19], α-retrovirus Rous sarcoma virus (RSV) [20], lentivirus maedi-visna virus (MVV) [7], and lentivirus human immunodeficiency virus 1 (HIV-1) [21]. As three of the studies utilized single particle cryo-electron microscopy [7,19,21], much of the work benefited from the ongoing revolution in this structural biology platform (reviewed in [22]).…”
Section: Surprising Diversity Of Retroviral Intasome Architecturesmentioning
confidence: 99%
“…In contrast to this, both NTD and CTD of HIV A reaching dimer have to undergo sterically unfavorable rotation, translation and closure motions to attain the core dimer conformation. The flexibility of CCD-CTD linker due to its disordered nature is reported to be important for the proper functioning of IN by positioning the CTD in cis and trans to the neighboring monomer (Ballandras-Colas et al 2016; Yin et al 2016). The area and volume of the dimer interface is also higher in core dimer when compared to the reaching dimers (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to DNA binding, the inner monomeric subunits of PFV intasome are associated through the interactions between NTD of one monomer and CCD of another monomer, while the two outer monomeric units interact with the inner monomers by CCD-CCD interactions. The cryo-EM and X-ray studies of Mouse mammary tumour virus (MMTV) and Rous sarcoma virus (RSV) intasomes have reported an octameric state of IN bound to both viral and target DNA (Ballandras-Colas et al 2016; Yin et al 2016). Similar to the PFV intasome, the inner dimers of both MMTV and RSV express domain-swapping interactions, while the outer dimers provide CTDs to the inner dimers for integration in a trans fashion.…”
Section: Introductionmentioning
confidence: 99%